HUBUNGAN KADAR HbA1c DAN PROFIL LIPID DENGAN KEJADIAN STROKE ISKEMIK PADA PASIEN DIABETES MELITUS TIPE 2 DI RUMAH SAKIT BADAN PENGUSAHAAN BATAM - Andi Asda Astiah; Yusmahenry Galindra; Mukjizat Khiduar Mukzi (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: Ischemic stroke is one of the common macrovascular complications in patients with type 2 diabetes mellitus (T2DM). This study aims to determine the relationship between HbA1c levels and lipid profile with the incidence of ischemic stroke in T2DM patients at Badan Pengusahaan Batam Hospital. Methods: This research used a case-control design with a retrospective approach. The study sample consisted of 238 T2DM patients divided into two groups: the case group (patients with ischemic stroke) and the control group (patients without ischemic stroke). Data were collected from patient medical records, including HbA1c levels and lipid profiles (total cholesterol, LDL, HDL, and triglycerides). Data analysis was performed using the chi-square test to examine the relationship between independent variables (HbA1c levels and lipid profile) and the dependent variable (ischemic stroke). Results: There was a significant association between HbA1c levels >7.0% and the incidence of ischemic stroke (p=0.000; OR=3.497). Total cholesterol ≥200 mg/dL and LDL ≥130 mg/dL were also associated with an increased risk of ischemic stroke (p=0.000; OR=2.680 and OR=3.189, respectively). However, HDL and triglyceride levels did not show a significant association (p=1.00 and p=0.384). Conclusion: HbA1c levels, total cholesterol, and LDL were associated with the incidence of ischemic stroke in patients with type 2 diabetes mellitus. However, HDL and triglyceride levels did not show a significant association. Keywords : HbA1c, lipid profile, ischemic stroke, type 2 diabetes melitus